2011
DOI: 10.1159/000324864
|View full text |Cite
|
Sign up to set email alerts
|

Human Galectins Induce Conversion of Dermal Fibroblasts into Myofibroblasts and Production of Extracellular Matrix: Potential Application in Tissue Engineering and Wound Repair

Abstract: Members of the galectin family of endogenous lectins are potent adhesion/growth-regulatory effectors. Their multifunctionality opens possibilities for their use in bioapplications. We studied whether human galectins induce the conversion of human dermal fibroblasts into myofibroblasts (MFBs) and the production of a bioactive extracellular matrix scaffold is suitable for cell culture. Testing a panel of galectins of all three subgroups, including natural and engineered variants, we detected activity for the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 64 publications
(26 reference statements)
0
59
0
1
Order By: Relevance
“…There is controversy not only with respect to the presence of myofibroblasts in keloid tissues [2,4,8,44] but also over the conversion in vivo of dermal fibroblasts into myofibroblasts in wound healing induced by Gal-1 [24,26,45]. In fact, different studies in vivo have reported that myofibroblasts are the predominant cell type present in keloid tissues [4,44] while others report that they are absent [2,8] and that in animal models Gal-1 induces the conversion of dermal fibroblasts into myofibroblasts during wound healing [23,45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is controversy not only with respect to the presence of myofibroblasts in keloid tissues [2,4,8,44] but also over the conversion in vivo of dermal fibroblasts into myofibroblasts in wound healing induced by Gal-1 [24,26,45]. In fact, different studies in vivo have reported that myofibroblasts are the predominant cell type present in keloid tissues [4,44] while others report that they are absent [2,8] and that in animal models Gal-1 induces the conversion of dermal fibroblasts into myofibroblasts during wound healing [23,45].…”
Section: Discussionmentioning
confidence: 99%
“…There is controversy not only regarding the presence of myofibroblasts in keloid tissues [2,4,8,44] but also regarding the conversion of fibroblasts into myofibroblasts by Gal-1 [24,26,45]; therefore, we sought to determine by double-immunofluorescence staining whether α-SM actin, the most common marker for myofibroblasts identification [46], was present in the fibroblasts of keloid tissues examined. Immunolocalization demonstrated that α-SM actin was completely absent in the fibroblasts expressing Gal-1 as well as in those that did not it (Fig.…”
Section: In Vivo Gal-1 Immunolocalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Dvorankova et al demonstrated that in vitro administration of recombinant galectin-3 can trigger activation of myofibroblasts, with subsequent production of extracellular matrix, a finding which could be used in tissue engineering and wound repair [47]. Henderson et al explored the involvement of galectin-3 in the development of liver fibrosis, showing that myofibroblast activation and procollagen (I) expression is markedly reduced when the galectin-3 gene is supressed [48].…”
Section: Galectin-3 In Experimental Studiesmentioning
confidence: 99%
“…In the case of surgery and/or trauma the skin is damaged and the healing process needs to be started to restore the integrity of the organism as soon as possible. Wound healing includes a series of processes which include cell migration (Woodley et al 1993) proliferation, differentiation (Masur et al 1996;Morasso and Tomic-Canic 2005;Novotny et al 2011), and extracellular matrix formation (Clark 1990) including cell-cell and cell-matrix interactions (Adzick and Lorenz 1994;Werner et al 2007;Dvorankova et al 2011). Several molecules have been described which have significant modulatory roles in cell communication and thus have modulatory roles in tissue repair and regeneration processes (He and Baum 2006;Barrientos et al 2008;Zaja-Milatovic and Richmond 2008;Hu et al 2009;Yaman et al 2010).…”
mentioning
confidence: 99%